2017
DOI: 10.1111/ped.13418
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric respiratory tract diseases: Chronological trends and perspectives

Abstract: Background: The aim of this study was to describe the epidemiological profile of childhood respiratory tract diseases (RTD) in the region of Sfax, Tunisia, and to evaluate their trends over a 13 year period. Methods: We conducted a retrospective study of all children hospitalized with RTD aged under 14 years. We collected data from the regional morbidity register of the university hospital of Sfax from 2003 to 2015.Results: A total of 10 797 RTD patients were enrolled from 49 880 pediatric hospitalizations (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…This was ascribed, for example, to immunological immaturity and reduced airway caliber, along with greater exposure to risk factors among boys at this age. 4,11,12 The findings showed that there was a significant positive correlation of PM 2.5 levels with pneumonia hospitalizations. This had also been reported in studies conducted in Brazil by Machin and Nascimento, 13 in the city of Cuiabá, and by Negrisoli and Nascimento, 14 in the city of Sorocaba.…”
Section: Discussionmentioning
confidence: 84%
“…This was ascribed, for example, to immunological immaturity and reduced airway caliber, along with greater exposure to risk factors among boys at this age. 4,11,12 The findings showed that there was a significant positive correlation of PM 2.5 levels with pneumonia hospitalizations. This had also been reported in studies conducted in Brazil by Machin and Nascimento, 13 in the city of Cuiabá, and by Negrisoli and Nascimento, 14 in the city of Sorocaba.…”
Section: Discussionmentioning
confidence: 84%
“…When heterogeneity was not significant ( P ≥ .10 or I 2 < 50%), a fixed effects model was used to analyze the pooled effect, and when heterogeneity was statistically significant ( I 2 ≥ 50% or P < .10), a random effects model was used Reasons for heterogeneity were explored by subgroup analysis. [ 13 ] During the research process, researchers explored the root causes of heterogeneity through sensitivity analysis. In case of serious heterogeneity, check whether the data are correct again, such as whether there are errors in the analysis unit, or properly exclude a small number of related studies on possible sources of heterogeneity, so as to effectively reduce heterogeneity.…”
Section: Methods and Analysismentioning
confidence: 99%